Design and Fabrication of Stamp Canting Based on Fused Deposition Modeling and Electroforming Technology - Setiawan, Joni; Sudiarso, Andi; Winursito, Isananto; Herliansyah, Muhammad Kusumawan (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2024)
The demand for canting stamps continues to increase along with the development of batik. This need cannot be met by canting cap producers because their productivity is low as a result of the process of making canting caps still being manual. This research developed a canting cap using the conductive material Acrylonitrile Butadiene Styrene (ABS)–electroformed by copper (CABS-EBC). The research procedure consists of 1) design and 3D-printing procedure and 2) electroforming and assembling procedure. Design and 3D-printing procedures consist of preparation steps, designing, slicing process, and printing process. Electroforming procedure consists of preparation, pre-treatment, electroforming. Then proceed with the assembly steps. The process is depicted through diagrams, pictures/photos and explained step by step. From the experimental results it can be concluded that canting caps can be made using conductive ABS and copper electroforming materials